Valorization of Char From Biomass Gasification as Catalyst Support in Dry Reforming of Methane - Benedetti, Vittoria; Ail, Snehesh Shivananda; Patuzzi, Francesco; Baratieri, Marco (Frontiers in Chemistry, 2019)
This study responds to the need of finding innovative routes for valorizing char derived from biomass gasification. Char is currently treated as a waste representing an energetic and economic loss for plant owners. However, it displays many similarities to activated carbon (AC) and could replace it in several applications. In this regard, the current work investigates the use of gasification derived char as catalyst support in dry reforming of methane (DRM) reactions. Char collected from a commercial biomass gasifier currently in operation was characterized and employed for the synthesis of cobalt catalysts. The catalysts were characterized and tested in an atmospheric pressure fixed bed reactor operating at 850 °C with CH4:CO2 = 1 and a weight hourly space velocity of 6500 mL g-1 h-1. The effectiveness of the synthesized catalysts was defined based on CO2 and CH4 conversions, the corresponding H2 and CO yields and their stability. Accordingly, catalysts were synthesized with cobalt loading of 10, 15 and 20 wt.% on pure and HNO3 treated char, and the catalyst with optimum comparative performance was promoted with 2 wt.%MgO. Catalysts prepared using pure char showed low average conversions of 23 % and 17 % for CO2 and CH4, yields of 1 % and 14 % for H2 and CO, and deactivated after few minutes of operation. Higher metal loadings corresponded to lower conversion and yields. Although HNO3 treatment slightly increased conversions and yields and enhanced the stability of the catalyst, the catalyst deactivated again after few minutes. On the contrary, MgO addition boosted the catalyst performances leading to conversions (95 % and 94 % for CO2 and CH4) and yields (44 % and 53 % for H2 and CO) similar to what obtained using conventional supports such as Al2O3. Moreover, MgO catalysts proved to be very stable during the whole duration of the test.